2009
DOI: 10.1371/journal.pone.0005182
|View full text |Cite
|
Sign up to set email alerts
|

Smoothened Adopts Multiple Active and Inactive Conformations Capable of Trafficking to the Primary Cilium

Abstract: Activation of Hedgehog (Hh) signaling requires the transmembrane protein Smoothened (Smo), a member of the G-protein coupled receptor superfamily. In mammals, Smo translocates to the primary cilium upon binding of Hh ligands to their receptor, Patched (Ptch1), but it is unclear if ciliary trafficking of Smo is sufficient for pathway activation. Here, we demonstrate that cyclopamine and jervine, two structurally related inhibitors of Smo, force ciliary translocation of Smo. Treatment with SANT-1, an unrelated S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
109
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 39 publications
10
109
0
Order By: Relevance
“…A number of mutations encoding IFT proteins involved in predominantly primary cilium anterograde IFT have been described, resulting in mice with Hh loss of function phenotypes (Huangfu et al, 2003;Cortellino et al, 2009). Several Hh components, including SMO and Gli molecules, are also present at the primary cilium upon Hh stimulation Rohatgi et al, 2009;Wang et al, 2009;Wilson et al, 2009a). An SMO mutant lacking ciliary translocation blocks Hh signaling (Corbit et al, 2005).…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of mutations encoding IFT proteins involved in predominantly primary cilium anterograde IFT have been described, resulting in mice with Hh loss of function phenotypes (Huangfu et al, 2003;Cortellino et al, 2009). Several Hh components, including SMO and Gli molecules, are also present at the primary cilium upon Hh stimulation Rohatgi et al, 2009;Wang et al, 2009;Wilson et al, 2009a). An SMO mutant lacking ciliary translocation blocks Hh signaling (Corbit et al, 2005).…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…Gli3 processing is significantly affected by IFT mutants (Huangfu and Anderson, 2005;May et al, 2005;Cortellino et al, 2009), suggesting that SMO activates downstream molecules at the cilium. Current data indicate that localization of SMO to cilium is not sufficient to activate hedgehog signaling (Rohatgi et al, 2009;Wilson et al, 2009a). Using Kif3a tissue-specific gene knockout, recent studies revealed dual roles of cilium for hedgehog signaling carcinogenesis in mouse models Wong et al, 2009).…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…Several studies have now confirmed that Smo appears to concentrate within the primary cilium upon Hh stimulation or upon treatment with pharmacological agents such as cyclopamine or SAG1 that bind Smo and either antagonize or stimulate its activity (22)(23)(24)(25)(26). A prominent concentration of Gli1, Gli2, and Gli3 at the tip of the cilium regardless of treatment with ShhN has been noted in cells virally transduced for expression of these proteins, and endogenous Gli3 has been detected at the ciliary tip in cultured primary limb bud cells in the absence of exogenous Hedgehog stimulation (27).…”
mentioning
confidence: 99%
“…The PKA phosphorylation sites are not conserved in vertebrate Smo (Zhang et al, 2004). However, recent studies have shown that activation of PKA by cholera toxin or forskolin treatment can induce the accumulation of Smo in the proximal part of the cilium (Wilson et al, 2009;Milenkovic et al, 2009;Wen et al, 2010). Moreover, inhibition of PKA activity using small molecule inhibitors can block Shh-induced activation of ptc1 and gli1 (Milenkovic et al, 2009).…”
Section: Cxcr4a Inhibits Pka Activitymentioning
confidence: 99%